Drainage basin morphometry of the Encadenadas del Oeste lakes, Argentina - Geraldi, Alejandra Mabel (2016)
The Las Encadenadas basin can be defined as an endorheic fluviolacustrine system. The aim of this study is to identify hydrographic sectors and subbasins within the Encadenada’s drainage basin and analyze the former’s morphometric properties including hypsometry. The morphometric analysis allowed for quantification of variables and indices for example area, perimeter, total length of streams, etc. Hypsometric curves were also plotted for each subbasin and finally, principal components analysis was used to sort basins based on results from individually calculated parameters and indices. This study’s aim was to define for the first time the various drainage subbasins that comprise the Encadenadas del Oeste’s basin. The characterization of these units shows that the basin is morphologically diverse due to the dynamic fluvial activity that prevails within its limits. One of the above mentioned morphological units are the alluvial cones which form at the mouths of the mainstreams and delineate the bases of the different subbasins. The drainage network exhibits overall a low level of ramification and hierarchy which is likely due to the sedimentary nature and high permeability of the sub-surface soil.